Psychological Harmony and Conflict in Minority Group Ties - Sherif, Muzafer (The American catholic sociological review, 1961)
Problems concerning the psychological ties to minority groups in the sense of belongingness have been related to the concept of identification. In the discussion of this general matter some social processes are considered which are subsumed under the individual's experiences relative to the social scheme in which he moves. Particular emphasis is placed on the application of generalizations involving individual psychological phenomena as they seem to apply to minority group membership.